2017
DOI: 10.1016/j.seizure.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and tolerability of Perampanel in children, adolescents and young adults with refractory epilepsy: A UK national multicentre study

Abstract: Perampanel was fairly effective in a heterogeneous group of 96 children and adolescents with very refractory epilepsy. The rate of adverse events leading to discontinuation was considerable in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 26 publications
4
33
1
2
Order By: Relevance
“…In contrast, an Italian study found that the proportion of responder patients was higher in patients taking enzyme-inducing antiepileptic drugs than in those taking nonenzyme-inducing antiepileptic drugs. However, the majority of prior observational studies have reported no significant difference in the PER responder rate between patients undergoing concomitant treatment [31,[36][37][38], which is consistent with our observations. The diverse results suggest that the effect of concomitant enzyme-inducing antiepileptic drugs on PER may vary in real-world settings.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, an Italian study found that the proportion of responder patients was higher in patients taking enzyme-inducing antiepileptic drugs than in those taking nonenzyme-inducing antiepileptic drugs. However, the majority of prior observational studies have reported no significant difference in the PER responder rate between patients undergoing concomitant treatment [31,[36][37][38], which is consistent with our observations. The diverse results suggest that the effect of concomitant enzyme-inducing antiepileptic drugs on PER may vary in real-world settings.…”
Section: Discussionsupporting
confidence: 92%
“…A similar responder rate was observed in 24 adolescents in a Canadian center over a median treatment duration of 59 weeks [26]; however, no patients achieved sustained seizure freedom. Recently, a United Kingdom national multicenter observational study in a heterogeneous group of 96 children and adolescents with highly refractory epilepsy who underwent PER treatment reported an overall responder of 18.8% for all seizure types at both 6-and 12-month follow-ups [31]. Our data were generally consistent with previous reports of broadly similar responder and seizure-free rates for the overall core study population.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations